Business model transformation of REITs in the senior housing sector - Yoo, Jii; Jeon, Jae Sik (International Journal of Strategic Property Management, 2024)
This study examines the transformative impact of the REIT Investment Diversification and Empowerment Act (RIDEA) of 2007 on Real Estate Investment Trusts (REITs) and their partnerships with operating entities in the U.S. senior housing industry. We explore how REITs, functioning as both asset owners and managers, adapt their business strategies in response to the evolving business landscape. Employing a case study approach rooted in Zott and Amit’s (2010) conceptualization of business models, the study identifies and analyzes notable shifts in market participants’ recognition of value-enhancing approaches, encompassing not only traditional rental income but also the operational performance of property managers. The findings reveal an expanded risk and profit-sharing mechanism propelled by the newly implemented business framework based on RIDEA, fostering enhanced alignment of interests between REITs and operators compared to the traditional business framework. While this effect under the new model holds the potential for significant enhancements in operational efficiency for asset managers, it concurrently introduces complexities arising from heightened financial and market risks, as well as challenges related to workforce management. Our findings offer valuable insights to industry experts, including REITs, operators, investors, and policymakers, enriching their comprehension of the evolving business models within the senior housing sector.